Soil nutrients, microbial biomass, and crop response to organic amendments in rice cropping system in the Shiwaliks of Indian Himalayas - Richa Rajput; Priya Pokhriya; Pooja Panwar; A. Arunachalam; Kusum Arunachalam (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose Intensive agriculture activities in small holder farming systems are declining over all soil nutrient status. The present study is conducted to compare the soil health and plant growth attributes under rice cultivation among different organic amendments. Recycled waste of rice–wheat agrosystem is utilized to determine optimal sustainable solution for hilly areas. Methods Randomly blocked design experiment was conducted with rice plants, each amended with organic inputs including rice straw residue (T1), rice biochar (T2), rice compost (T3), wheat straw residue (T4), wheat biochar (T5), wheat compost (T6), mix of wheat + rice compost (T7), green manure (T8) and control (no amendment). Soil samples were studied at each growth phase while plant growth attributes were measured at the harvesting stage of the crop. Results T6 and T7 have shown significantly higher magnitude of soil organic carbon, microbial biomass carbon, microbial quotient, available nitrogen, and enzymatic activities (dehydrogenase, alkaline phosphatase and urease) than biochar (T2 and T5) and crop residue amendments (T1, T4 and T8). An increase of up to 47% was obtained in cumulative growth attributes (plant height, total biomass, and a number of tillers, spikes, and spike length) of rice plant in T6 amendment. The principal component analysis revealed two components responsible for 54.17% of the variance in the organically treated soil. Conclusion The experimental results imply that composting of crop residues could be the most reliable practice to improve soil nutritional quality as well as crop growth for sustainable rice–wheat cropping system in the hilly area.